Sharia Financial Literation In Developing Sharia-Based Business For Rural Communities In South Sulawesi - Abdullah, Muh. Wahyuddin; Kadir, Syahruddin; Alaaraj, Hassan (IKONOMIKA, 2020)
This study aims to determine the understanding and public trust about Islamic products and Islamic banking and to determine the prospects for Islamic finance in rural business development. The methodology used is descriptive qualitative through FGD and data triangulation. The results showed that people in rural areas tit belongs to less literate and less of trust because some people only understand the Islamic banking products used and only consider aspects of the needs and virtues of banking service facilities. However, it indicates a bright prospect for developing a sharia-based community business with residents of the region who are aware of Islamic law and the demand for Islamic financial institution services by the community is increasing.Keywords: Literacy, Islamic Finance, Business.